Shari'ah appraisal of islamic currency hedging facilities : a proposal for an alternative model - Agha, Syed Ehsanullah
Volatility in global financial markets made 'exchange rate risk' a disturbing phenomenon in the modern age for financial and non-financial institutions alike. As firms expand businesses beyond their original jurisdictions, they are exposed to many types of risks including exchange rate risk. Islamic financial institutions (IFIs) are also exposed to this risk like their conventional peers. Several hedging products have been developed through Islamic financial engineering such as Islamic FX forwards, Islamic options, Islamic swaps etc. which are being utilized by IFIs to hedge their exposure to FX risk and to accommodate their customers in mitigating FX risk. However, a review of the existing literature reveals that despite the Sharīʻah resolutions on the legality of hedging and its mechanism, the contemporary hedging practices in Islamic finance industry are still controversial in their design and operations. This study aimed to critically analyze contemporary Islamic currency hedging facilities from a Sharīʻah perspective using qualitative research method. The research found that these products are heavily criticized due to the involvement of (1) zero-sum-game, (2) tawarruq, (3) currency salam, and (4) the absence of actual loss determination mechanism in the event of premature termination and mark-to-market computation. Furthermore, the problematic nature of these products resulted in its low adoptability (10-15%) in hedging markets due to high cost and sophisticated documentation. To address these challenges, the present study proposed a cooperative currency-hedging model (CCHM) where the concept of mutual risk sharing with the integration of cash waqf has been advocated. A financial simulation run on the historical data of the State Bank of Pakistan showed the commercial adoptability of this model. To further examine viability of the model, semi-structured interviews were conducted with selected Sharīʻah scholars, academicions, regulators and practitioners. The informants considered CCHM as a viable alternative of contemporary Sharīʻah compliant hedging products. Besides some challenges in the model which requires further research, the informents were satisfied with the Sharīʻah structure and business model of CCHM. Among other aspects of the model, zero-sum free hedging, mutual risk sharing and the integration of cash waqf gained special appreciation from the interviewees. The development of such a cooperative hedging mechanism would facilitate IFIs as they participate in the global financial market. The findings might enable Islamic financial engineers to avoid Sharīʻah non-compliance risk in developing hedging products. The future research may focus on utilising Islamic cooperative contracts (due to their flexible nature) to address some of the complicated business needs of modern commercial world.